Decisão judicial, instituições e estrutura socioeconômica: por uma análise política do pensamento jurídico brasileiro (2009)
This article presents an investigation about the matters that rules the inquiries on habeas corpus between the Second Kingdom and the First Republic in Brazil, and proposes a conceptual frame to characterize the constitutional though made by the Tribunal from the analysis of their decisions.